Pelatihan Pembuatan Lilin Aromaterapi dan Deterjen Cair Berbasis Potensi Lokal: Upaya Mendukung Kegiatan Pesantrenpreneur Zainul Hasan Genggong Probolinggo - Nurul Hidayat; Siti Nur Seha; ST. Ulfawanti Intan Subadra; Hendra Susanto; Markus Diantoro; Sunaryono; Ahmad Taufiq (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
The entrepreneurship movement is one of the government's efforts to address the increasing unemployment problem. High innovation and creativity skills are essential in entrepreneurship. Moreover, Indonesia is abundant in local potential that can serve as material for entrepreneurship. However, not all people have an understanding of the local potential to be used as eco-souvenirs. This is also faced by the Pondok Pesantren Zainul Hasan Genggong. The Pondok Pesantren Zainul Hasan Genggong is able to produce used cooking oil waste reaching around 3,105 liters per day, but this waste is not utilized and is only dumped into the environment. In addition, in the Pesantren area, there are also quite a lot of moringa leaves available, but they are only used as fences. To overcome the existing problems, the community service team of the State University of Malang (UM) conducted training to utilize used cooking oil and moringa leaves as eco-souvenirs in the form of aromatherapy candles and liquid detergents. This activity was carried out using lecture and practice methods, which began with pre-training activities. Pre-training was carried out with the aim of providing insight into the basics of entrepreneurship. Furthermore, training was carried out on making liquid detergent and aromatherapy candles. In addition to providing insight into the making of the two products, the research team also provided participants with information on how to present and sell products directly to the general public. Evidently, participants succeeded in selling the aromatherapy candle products they made for 30 minutes. This series of training was followed with great enthusiasm, actively, and interactively. The evaluation results showed a good response from the participants as a whole. The material is in accordance with the practice and needs of the cottage. This shows that the eco-souvenir making training activity was successfully carried out well and had a significant impact on the participants.